Strategi Manajemen Perpustakaan iBI Library Dalam Meningkatkan Efisiensi Layanan Melalui Aplikasi Mobile - Amaliah, Eni; Saputra, Julian Hadi; Febrian, Muhammad Kadavi (Baitul ’Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
The development as well as advances in information and communication technology, modern libraries need to adapt in order to meet the needs of users, especially through the use of mobile applications. This research aims to examine the library management strategies used by iBI Library. It is an application released by Bank Indonesia in utilizing mobile applications to improve the efficiency of library services. The method used is a qualitative approach with a literature study, including analysis of various relevant sources. The results showed that iBI Library implemented a management strategy that includes planning, organizing, and routine evaluation. The mobile application developed allows users to access information quickly and efficiently, and strengthens the interaction between librarians and users. Even so, challenges such as mastery of application features and the need for better socialization still have to be overcome. This study recommends further development of technology-based library services and emphasizes the importance of training for staff for optimal use of the application. In this way, iBI Library can serve as an example for other libraries in integrating technology to improve services and relevance.